If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(4x + -6) = 8x + 5(8x + -6) Reorder the terms: 12(-6 + 4x) = 8x + 5(8x + -6) (-6 * 12 + 4x * 12) = 8x + 5(8x + -6) (-72 + 48x) = 8x + 5(8x + -6) Reorder the terms: -72 + 48x = 8x + 5(-6 + 8x) -72 + 48x = 8x + (-6 * 5 + 8x * 5) -72 + 48x = 8x + (-30 + 40x) Reorder the terms: -72 + 48x = -30 + 8x + 40x Combine like terms: 8x + 40x = 48x -72 + 48x = -30 + 48x Add '-48x' to each side of the equation. -72 + 48x + -48x = -30 + 48x + -48x Combine like terms: 48x + -48x = 0 -72 + 0 = -30 + 48x + -48x -72 = -30 + 48x + -48x Combine like terms: 48x + -48x = 0 -72 = -30 + 0 -72 = -30 Solving -72 = -30 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 | | y=x^2+12+35 | | 5-3x=4x+12 | | 6-3A+5B=0 | | (-9x+11)8= | | 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 |